Genetic inactivation of ANGPTL4 improves glucose homeostasis and is associated with reduced risk of diabetes - Viktoria Gusarova (Nature Portfolio, 2018)
Genetic variation in ANGPTL4 is associated with lipid traits. Here, the authors find that predicted loss-of-function variants in ANGPTL4 are associated with glucose homeostasis and reduced risk of type 2 diabetes and that Angptl4 −/− mice on a high-fat diet show improved insulin sensitivity.